Sesja plenarna IEfficacy and safety of topical calcineurin inhibitors in the treatment of atopic dermatitis - Silny, Wojciech; Czarnecka-Operacz, Magdalena (Dermatology Review/Przegląd Dermatologiczny, 2009)
This paper presents new therapeutic approaches in atopic dermatitis (AD) in terms of topical treatment with calcineurin inhibitors. Cyclosporin A due to its high molecular weight is not used in the topical therapy of AD. However, as a solution it has been introduced to ophthalmology and also it has been successfully used for the treatment of various disorders within mucous membranes of the oral cavity. Tacrolimus ointment 0.03 and 0.1% as well as pimecrolimus are effective topical therapeutic agents in the treatment of inflammatory skin lesions in AD. In our opinion topical calcineurin inhibitors may be successfully used in all age groups of AD patients, in both the acute and chronic stage of the disease and within all body regions including the face and neck. Studies performed by Reitamo have demonstrated that twice or three times weekly proactive application of tacrolimus is sufficient to control the occurrence of flares in AD patients. These results are strong evidence of a novel management option for patients suffering from this disease.We have also presented the updated opinion of specialists concerning adverse effects and safety of topical treatment of AD patients with calcineurin inhibitors. According to our knowledge and personal experience this group of topical agents seems to be safe and effective in case of patients suffering from AD.